Diagnóstico e proposições para a gestão participativa e integrada dos resíduos sólidos urbanos no município de Passo Fundo, RS - Gomes, Aline Pimentel (2011)
The problems caused by solid waste have worsened in recent decades, due to the amount generated and the changes in its composition. In most Brazilian cities, the municipal authorities just collect and dispose the waste, often inadequately. The city of Passo Fundo, RS is included in this statistic, which explains this research that aims to diagnose the current municipal solid waste management system and propose actions for participatory and integrated management in order to minimize environmental, health and social problems caused in the city. Data about solid waste management and the work of the recyclable scavengers were collected in the municipal agencies, in charities and with the recyclable scavengers, through direct observations, document reviews, interviews and forms. The results demonstrate the lack of technical capacity of public administration, the absence of public policies related to solid waste and lack of awareness of the population that does not make source separation. In addition, the municipality does not have a composting plant, the existing recyclables sorting plant has been operated inadequately and the situation of the landfill is precarious. The number of recyclable scavengers in the city is significant, including youth and children, who mainly work independently, in poor conditions, they have to travel long distances to collect recyclable waste in the downtown area, have low education and most have the collecting activity as only source of income, whose value is below the minimum wage. The price of recyclable paid to scavengers is low due the large number of middlemen and the long distance to the recycling industry. The proposed actions will help to solve the environmental, health and social problems caused by municipal solid waste in the city, and if they were implemented, there will be improvements in environmental preservation, urban sanitation, public health, life quality of population and work and life conditions of recyclable scavengers